EFEKTIVITAS TEKNIK FADING DENGAN MEDIA BONEKA TANGAN DALAM MENURUNKAN PERILAKU MENANGIS AKIBAT PERPISAHAN PADA ANAK USIA DINI: STUDI SUBJEK TUNGGAL DI PAUD LAB SCHOOL UNIVERSITAS NEGERI PADANG - Jantika, Gita; Feny Rahayu, Wirza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Crying behavior due to separation anxiety in early childhood is still a challenge in the adaptation process in the school environment, while interventions that integrate behavioral approaches and play media are still limited. This study aims to test the effectiveness of fading techniques with hand puppet media in reducing crying behavior in 4-year-old children at the PAUD Lab School, Padang State University. This study uses a single-subject experimental method with an A–B–A' design, which includes the baseline, intervention, and post-intervention stages. Data collection was carried out through observation and interviews with a focus on the duration of crying behavior when the child was separated from his parents. Intervention is provided through gradual exposure supported by the use of hand puppet media as a means of storytelling. The data was analyzed using visual analysis including changes in levels, trends, and overlaps between phases. The results showed a consistent decrease in the duration of crying behavior, from 28–24 minutes in the baseline phase to 22–13 minutes in the intervention phase, and further decreased to 12–5 minutes in the post-intervention phase. These findings show that the integration of fading techniques and hand puppet media is effective in supporting children's emotional regulation and can be an applicable intervention strategy in the context of early childhood education.